The Impact Of Experiential Learning To Improve Student's Ability In Reading Recount Text - Ajeng Yunica Hanifa; Wahyu Satya Gumelar; Andriana Gaffar (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
This study investigates the effectiveness of experiential learning in improving students' ability to read recount texts. Addressing the challenges faced by students with traditional teaching methods, the research implemented experiential learning strategies to enhance comprehension. Using a one-group pretest-posttest design with 26 male students from SMK 2 LPPM RI Majalaya, the study found significant improvements in reading scores, with averages increasing from 63.35 to 81.42. The frequency distribution also shifted positively post- intervention. Normality tests confirmed the validity of the parametric analyses. The findings indicate that experiential learning effectively enhances students' reading comprehension of recount texts, suggesting its potential for broader educational application. Future research should explore its long-term impact and applicability across diverse student groups